Racial and ethnic disparities in coronavirus disease 2019 disease incidence independent of comorbidities, among people with HIV in the United States. (1st July 2022) - Ignacio, Rachel A. Bender; Shapiro, Adrienne E.; Nance, Robin M.; Whitney, Bridget M.; Delaney, Joseph A.C.; Bamford, Laura; Wooten, Darcy; Karris, Maile Y.; Mathews, William C.; Kim, Hyang Nina; Keruly, Jeanne; Burkholder, Greer; et al.
Abstract : Objectives: To define the incidence of clinically detected coronavirus disease 2019 (COVID-19) in people with HIV (PWH) in the United States and evaluate how racial and ethnic disparities, comorbidities, and HIV-related factors contribute to risk of COVID-19. Design: Observational study within the CFAR Network of Integrated Clinical Systems cohort in seven cities during 2020. Methods: We calculated cumulative incidence rates of COVID-19 diagnosis among PWH in routine care by key characteristics including race/ethnicity, current and lowest CD4 + cell count, and geographic area. We evaluated risk factors for COVID-19 among PWH using relative risk regression models adjusted with disease risk scores. Results: Among 16 056 PWH in care, of whom 44.5% were black, 12.5% were Hispanic, with a median age of 52 years (IQR 40–59), 18% had a current CD4 + cell count less than 350 cells/μl, including 7% less than 200; 95.5% were on antiretroviral therapy (ART), and 85.6% were virologically suppressed. Overall in 2020, 649 PWH were diagnosed with COVID-19 for a rate of 4.94 cases per 100 person-years. The cumulative incidence of COVID-19 was 2.4-fold and 1.7-fold higher in Hispanic and black PWH respectively, than non-Hispanic white PWH. In adjusted analyses, factors associated with COVID-19 included female sex, Hispanic or black identity, lowest historical CD4 + cell count less than 350 cells/μl (proxy for CD4 + nadir), current low CD4 +  : CD8 + ratio, diabetes, and obesity. Conclusion: Our results suggest that the presence of structural racial inequities above and beyond medical comorbidities increased the risk of COVID-19 among PWH. PWH with immune exhaustion as evidenced by lowest historical CD4 + cell count or current low CD4 +  : CD8 + ratio had greater risk of COVID-19.